Prunus yunkaishanensis (Rosaceae), a new species from Guangdong, South China - Wu, Bao-Huan; Zhao, Wan-Yi; Yang, Hai-Jun; Chen, Zhi-Hui; Li, You-Yu; Cui, Da-Fang; Liao, Wen-Bo; Kang, Ming (Phytotaxa, 2022)
Prunus yunkaishanensis, a new species of Prunus subg. Laurocerasus (Rosaceae), is described and illustrated. The new species is similar to P. phaeosticta and P. fordiana in their leaves with punctate abaxial surface, but it can be distinguished from the latter two species by having larger leaves with more pairs of lateral veins, shorter inflorescences with stout rachises, bracts persistent during anthesis, and ovoid fruits.